Identification of resistance in mungbean cultivars against viral disease complex by use of cluster analysis - AND A.K. RAHEJA, O.P. SHARMA, PRAVEEN ARORA (Indian Phytopathology, 2002)
Genetic similarity and/or dissimilarity among genotypes, phenotypes of phytopathogenic organisms and gene-for-gene relationship can be exactly expressed by cluster analysis. The application of a definite hierarchical agglomerative clustering based on N connected clusters as a mean for describing genetic structure of mungbean (Vigna radiata) responsible for resistance and susceptibility towards bean common mosaic virus and crinkle virus diseases is discussed. A correlative structure was observed among both diseases and the dendrogram using cluster procedure was used to visualize the inter-relationship of the multiple disease complex with stable host gene for resistance. These information will greatly assist the planning of subsequent control strategies involving breeding for resistance.